Crisis Communication During Floods and the Media Landscape of the Republic of Armenia (The Case of Lori and Tavush Regions, 2024) - Abrahamyan, Lianna (Bulletin of Yerevan University B: Philology, 2026)
The article analyzes the role of crisis communication during the floods that occurred in Armenia in May 2024, using the developments in Lori and Tavush regions as case studies. The author identifies three communication phases: the initial information vacuum, the activation of social media, and the stabilization of official communication. The article examines the impact of media on shaping public trust, behavior, and perceptions, while also emphasizing the risks of misinformation dissemination. The analysis is carried out from the perspective of chaos theory and the dynamics of information flows. It is noted that communication between state authorities, the media, and the public needs improvement to ensure a more effective response to similar crises in the future.
Keywords: Misinformation,; crisis communication; natural disaster; framing; social media; chaos theory